Expectations About Satiety and Thirst Are Modified by Acute Motivational State - Yeomans, Martin R.; Chambers, Lucy; McCrickerd, Keri (Frontiers in Psychology, 2018)
Prior research has shown that consumers have clear and measurable expectations about the likely effects of food and drink items on their appetite and thirst, which are acquired with experience and influenced by a product’s taste and texture. What is unclear is whether expression of these expectations also varies with current appetitive state. It is possible that current appetite could increase or decrease the relevance of these expectations for future food choice and magnify a product’s expected impact on appetite. To test this, we contrasted expectations about satiety and thirst for four products consumed 2 h after an appetite manipulation at breakfast, achieved through ad libitum access to low-energy drinks only (hunger condition), cereal only but no drinks (thirst condition) or both foods and drinks (sated condition). The test products were two soups and two drinks, with a thicker and thinner version of each product type to act as positive control to ensure sensitivity in detecting differences in expectations. For satiety, the predicted differences between products were seen: soups and thicker products were expected to be more filling and to suppress subsequent hunger more than drinks and thinner products, but these differences were more pronounced in the hunger than thirsty or sated conditions. Being thirsty also enhanced expectations of how much drinks would appease immediate thirst. Overall the data show that expectations were adjusted subtly by a person’s current appetitive state, suggesting that we have mechanisms that highlight the most important features of a product at the time when it may be most beneficial to the consumer.